View of Independence Square, Trinidad, W.I. - (:unkn) unknown (My University, 2010)
View of Independence Square, Port of Spain, Trinidad
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns-- (name); Automobiles; Independence Square; Pedestrians; Port of Spain